Policies Governing Use of Computing Technology in Academic Libraries - Vaughan, Jason (Information Technology and Libraries, 2017)
The networked computing environment is a vital resource for academic libraries. Ever-increasing use dictates the prudence of having a comprehensive computer-use policy in force. Universities often have an overarching policy or policies governing the general use of computing technology that helps to safeguard the university equipment, software, and network against inappropriate use. Libraries often benefit from having an adjunct policy that works to emphasize the existence and important points of higher-level policies, while also providing a local context for systems and policies pertinent to the library in particular. Having computer-use policies at the university and library level Helps provide a comprehensive, encompassing guide for the effective and appropriate use of this vital resource.